Hexahydro-1H-Isoindolinone-Like Scaffolds from Electronically Deactivated and Sterically Hindered Dienes: Synthesis in the Context of Muironolide A - Olson, Christopher A.; Shaner, Courtnay E.; Roche, Sydney C.; Ferrence, Gregory M.; Mitchell, T. Andrew (Synthesis, 2015)
Initial synthetic efforts toward muironolide A based upon an intramolecular Diels–Alder strategy were hampered by a conjugate reduction rather than the desired half-reduction. An intermolecular Diels–Alder strategy was initiated that utilized electronically deactivated and sterically hindered dienes. The [4+2] cycloadditions were successful, but only with highly reactive dipolarophiles such as N-phenylmaleimide and 4-phenyl-1,2,4-triazoline-3,5-dione thus establishing the scope of these dienes. Although limited, installation of the α,β-unsaturated lactam embedded in the hexahydro-1H-isoindolinone is noteworthy.
Keywords: cycloaddition; Diels–Alder reaction; muironolide A; natural products; total synthesis